Augmented reality: Interactive and fun learning media to improve student learning outcomes - Anisyah, Siti; Imlessh, Mohammed Mahmoud Mohammed; Kusumaningrum, Selvy; Haryati, Nanik Sri; Santoso, Jarot Tri Bowo (Directorate of Research and Community ServiceUniversitas Negeri Yogyakarta, 2024)
Technological developments constantly bring various conveniences to all users, especially in the field of education. In education, technology plays a crucial role in developing innovative, creative, and informative learning methods. This research aims to analyze the role of Augmented Reality (AR) as an interactive and engaging learning medium to enhance student learning outcomes. This research involves experimental studies conducted on 52 accounting education students from the class of 2023 at Semarang State University. Data were collected using tests, questionnaires, and interviews. The data were analyzed using descriptive percentages and t-tests. The results of this research show that (1) AR media can be an effective and enjoyable interactive learning media. (2) Augmented Reality (AR) media has been shown to enhance student learning outcomes, with the average score increasing from 21.08 in the pretest to 70.60. This represents a significant improvement of 49.52 points. In addition, the results of the TAM analysis indicate that AR media is recommended for application in the learning process.